Ryzyko podatkowe oszacowania dochodu - Pasieczna, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the conditions of market economy enterprises are exposed to danger of several factors constituting general risk of commercial activity. The aim of this article is to present dangers and chances resulting from the regulations concerning adopting by a tax, body the institution of establishing businessman's income by means of estimation. The income estimation can be a result of e.g. unreliability of revenue and cost registers that is in the situation when the entries made in them do not reflect the actual state. The negligence of the registers results in tax effects on the ground of corporation income tax, personal income tax, lump sum of register income, goods and services tax. Besides, businessmen should take penal consequences into account. The introduction of new regulations concerning e.g., letting a taxpayer make some corrections of declarations after the end of a tax inspection is to simplify and shorten inspection proceedings which is a reflection of the realization by the legislator the demands of tax system reform which is to make Poland an enterprise-friendly country. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 317-323